PERAN AYAH DALAM PERKEMBANGAN DAN PENDIDIKAN ANAK: Studi di Kelurahan Labuhan Ratu Bandar Lampung - MUHASSIN, MOHAMMAD (Universitas Islam Negeri Raden Intan Lampung, 2016)
This research aims to describe the father’s roles in children’s development and education and the impact of the father’s involvement within their process. This is a descriptive qualitative research employing fathers in Kelurahan Labuhan Ratu Bandar Lampung as the informants taken by purposive sampling technique. The result of the research shows that the father’s roles in children’s development and education include teaching children on self-control and social values. In addition, the father’s involvement in children’s development and education gives a positive impact to the children’ cognitive, emotional, and social aspects, as well as their physical condition. Keywords: Father’s roles, children’s development, education